Acute traumatic coagulopathy in the setting of isolated traumatic brain injury: Definition, incidence and outcomes. (2nd January 2015) - Epstein, Daniel S.; Mitra, Biswadev; Cameron, Peter A.; Fitzgerald, Mark; Rosenfeld, Jeffrey V.
Abstract: Background and objectives. Acute traumatic coagulopathy (ATC) has been reported in the setting of isolated traumatic brain injury (iTBI) and associated with poor outcomes. Among patients with iTBI, we aimed to select an appropriate definition of ATC, outline the incidence of ATC and examine clinical variables associated with ATC. Methods. A retrospective review of The Alfred Trauma Registry was conducted and patients with iTBI (head AIS [Abbreviated Injury Score] ≥ 3 and all other body regions AIS < 3) were selected for analysis. The association of the international normalised ratio (INR) on arrival at hospital with the mortality on hospital discharge was explored, to select an appropriate clinical horizon to define ATC. The incidence of ATC was calculated using this definition. Injury and clinical variables measurable pre-hospital and immediately on arrival at the hospital were analysed to determine independent associations with ATC. Results. There were 1718 patients with iTBI included in the study. The overall mortality was 12%, but significantly greater when initial INR was measured at ≥ 1.3 (45.1%; p < 0.01). The proportion of patients with ATC, using this definition, was 7.7% (95% CI: 6.5–9.0). The pre-hospital variables independently associated with ATC in the setting of iTBI were age (OR 1.02, 95% CI 1.01–1.03), shock index (SI) of ≥ 1 (OR 1.68, 95% CI 1.01–2.79) and abnormal pupils (OR 8.33, 95% CI 4.50–15.89). The presence of at least two factors, of age > 50 yrs, SI ≥ 1, or abnormal pupils, was 97.54% (95% CI: 96.6–98.2) specific for ATC. Conclusions. An abnormal initial INR in the setting of iTBI was associated with poor outcomes, regardless of magnitude. The incidence of ATC appears too low to recommend empiric pro-coagulant management for all patients with iTBI. The subgroup of patients older than 50 yrs., with shock or abnormal size of pupils, may be considered for interventional trials of early treatment against ATC.